2021
DOI: 10.1021/jasms.0c00429
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lysophosphatidic Acid Measurement by Liquid Chromatography–Mass Spectrometry in COPD Patients

Abstract: Lysophospholipids are bioactive signaling molecules derived from cell membrane glycerophospholipids or sphingolipids and are highly regulated under normal physiological conditions. Lysophosphatidic acids (LPAs) are a class of lysophospholipids that act on G-protein-coupled receptors to exert a variety of cellular functions. Dysregulation of phospholipase activity and consequently LPA synthesis in serum have been linked to inflammation, such as seen in chronic obstructive pulmonary disease (COPD). The accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…LPA levels were not significantly associated with other baseline clinical variables in this study. Previously we reported that the majority of the LPA species, except LPA20:4, are higher in a small cohort of COPD patients compared to healthy controls [26]. It is unclear if COPD patients with low levels of LPA16 and LPA18 species in this study have significantly higher levels of these LPAs relative to healthy individuals, as samples from age-and sex-matched healthy subjects were not tested together with the COPD samples in the current study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…LPA levels were not significantly associated with other baseline clinical variables in this study. Previously we reported that the majority of the LPA species, except LPA20:4, are higher in a small cohort of COPD patients compared to healthy controls [26]. It is unclear if COPD patients with low levels of LPA16 and LPA18 species in this study have significantly higher levels of these LPAs relative to healthy individuals, as samples from age-and sex-matched healthy subjects were not tested together with the COPD samples in the current study.…”
Section: Discussionmentioning
confidence: 73%
“…LPA species were extracted using acidified butanol solvent as previously described [26]. Briefly, 10 µl of serum from each sample was pooled together as quality control samples.…”
Section: Mass Spectrometry Lpa Assaysmentioning
confidence: 99%
“…3 E) 6 , 17 . To confirm the release of LPA from these macrophages, macrophage-conditioned media was taken 30 min or 48 h after plating and various LPA species were measured by mass spectrometry 18 . We observed a significant increase in several LPA species over time.…”
Section: Resultsmentioning
confidence: 99%
“…By using 5% FBS in our culture media, these PLs were also introduced, but probably in much lower amounts than those added separately, although there seems to be no data available in the literature on FBS. Based on data from human serum or plasma, our serum-reduced culture medium contained the equivalent concentrations (nmol/mL) for LPC 16:0, LPC 18:0, LPC 18:1, LPA 16:0, and LPA 18:0 of approximately 3.6, 1.4, 0.9, 0.004, and 0.001 [ 41 , 42 ]. Whether the low PL concentrations added to the culture medium via 5% FBS already have an effect on FLS remains to be determined in further studies.…”
Section: Discussionmentioning
confidence: 99%